Risk Belief and Attitude Formation From Translated Scientific Messages About PFOA, an Environmental Risk Associated With Breast Cancer. Issue 3 (4th March 2017) - Smith, Sandi W.; Hitt, Rose; Russell, Jessica; Nazione, Samantha; Silk, Kami; Atkin, Charles K.; Keating, David
ABSTRACT: Evidence regarding possible environmental causes of breast cancer is advancing. Often, however, the public is not informed about these advances in a manner that is easily understandable. This research translates findings from biologists into messages at two literacy levels about perfluorooctanoic acid (PFOA), a possible environmental contributor to breast cancer. The Heuristic Systematic Model (HSM) was used to investigate how ability, motivation, and systematic and heuristic processing lead to risk beliefs and, ultimately, to negative attitudes for individuals receiving translated scientific messages about PFOA. Participants ( N  = 1, 389) came from the Dr. Susan Love Research Foundation's Army of Women. Findings indicated that ability, in the form of translated messages, predicted systematic processing, operationalized as knowledge gain, which was negatively associated with formation of risk beliefs that led to negative attitudes toward PFOA. Heuristic processing cues, operationalized as perceived message quality and source credibility, were positively associated with risk beliefs, which predicted negative attitudes about PFOA. Overall, more knowledge and lower literacy messages led to lower perceived risk, while greater involvement and ratings of heuristic cues led to greater risk perceptions. This is an example of a research, translation, and dissemination team effort in which biologists created knowledge, communication scholars translated and tested messages, and advocates were participants and those who disseminated messages.